INCREASING THE RESILIENCE OF THE COMMUNITIES OF KABANDUNGAN VILLAGE AND BARUJAMAS VILLAGE PADALUYU VILLAGE, CUGENANG SUB-DISTRICT, CIANJUR REGENCY THROUGH THE RECONSTRUCTION OF EARTHQUAKE-RESISTANT BUILDINGS AND POST-EARTHQUAKE AQUAPONIC FARMING - Shinta Aminda, Renea; Siregar, Tika Hafzara; Syaiful, Syaiful; Dwi Saputri, Dinda; Amelia, Anggi; Apriani, Lia; Anita Lestari, Puri; Leandra Damiana, Salma (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Padaluyu is one of the villages in Cugenang District, Cianjur Regency. Padaluyu Village has an area of approximately 595,110 ha. Currently, in the Padaluyu village area, Kampung Kabandungan RT 04/RW 03, Cugenang District, Cianjur Regency, there was an earthquake of Mw 5.6 on Monday, November 21, 2022. This event has resulted in damage to residents' houses, infrastructure, and residents' agricultural land. The purpose of this activity is to provide assistance to increase the resilience of the people of Kabandungan village and Barujamas village, Padaluyu village, Cugenang sub-district, Cianjur district through the reconstruction of earthquake-resistant buildings and post-earthquake aquaponic farming training. Improving the understanding of earthquake-resistant buildings is carried out through the presentation of earthquake-resistant building materials and visual simulations. Aquaponic farming training is carried out by exposing aquaponic farming material, making aquaponic buildings and installations, and practicing aquaponic farming. The result of this activity is that the people in RT 03 RW 04 and RT 03 RW 07 gain increased knowledge and understanding about the construction of earthquake-resistant housing which can be applied in the construction or repair of post-earthquake residents' houses. Residents' understanding of modern agriculture using the aquaponic method increases and residents can practice aquaponic farming by utilizing their yards to meet their food needs for vegetables and side dishes. The Head of Padaluyu Village hopes that this training can motivate the community to build houses and make very good use of vacant land.